Psicologia histórico-cultural na formação docente: estudo sobre a apropriação da obra de Vigotski em cursos de licenciaturas do Estado da Paraíba - Rasia, Maria da Guia Rodrigues (2009)
This thesis aims to understand how the appropriation of Vigotski‟s work has been done by Educational Psychology teachers in Pedagogy and Psychology Licentiature courses in the State of Paraíba. The research instruments interviews and syllabus course plans made it possible to analyse the manner of appropriation of Vigotski‟s works. The categories for appreciating the research data, outlined in the philosophical and methodological rationale regarding historical dialectic materialism, contained in Vigotski‟s work, were the following: contradiction, humanization, alienation, labor, objectivation, appropriation, totality and historicity. These categories are essential for understanding teacher education, if we see it as a human constitution process. The data analysis allowed us to identify the different levels of appropriation of Vigotskian theory, and it even showed the existence of a wide diversity of reading done by those who approach his fundamentals. The challenge presented to us, after the investigation, lies in facing the complexity of the articulation process in Historical-cultural Psychology, with teacher education in view. Such challenge means, not only contributing to the development of knowledge available in this area, but also enabling the teacher to give priority to the conceptual insight of Vigotskian‟s theory, unveiling new horizons towards the understanding of the meaning and relevance of human social history, and grasping the dynamic of the objectivating activity process in human beings. This research also points to the necessity of widening the applicability of such theoretical background, so that we can better contribute to the education of teachers and search for new possibilities of intervening in the social practice through education.